The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1093/tropej/fmx036
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oral Zinc Supplementation in Radiologically Confirmed Pneumonia: Secondary Analysis of a Randomized Controlled Trial

Abstract: There was no significant beneficial effect of zinc on the duration of recovery or risk of treatment failure in children with radiologically confirmed pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…Zinc supplementation was shown to reduce the respiratory morbidity of ALRI in children less than 5 years of age who were zinc deficient (8). Studies examining the clinical effects of zinc for treating pneumonia in children have shown conflicting results, with some studies showing a beneficial effect on the duration of recovery and severity but with other studies suggesting that zinc has no treatment benefit (9)(10)(11)(12)(13). Although the necessary role of zinc as a micronutrient in various physiological functions has been demonstrated, the molecular mechanism underlying the effects of zinc during viral infections has not been elucidated.…”
mentioning
confidence: 99%
“…Zinc supplementation was shown to reduce the respiratory morbidity of ALRI in children less than 5 years of age who were zinc deficient (8). Studies examining the clinical effects of zinc for treating pneumonia in children have shown conflicting results, with some studies showing a beneficial effect on the duration of recovery and severity but with other studies suggesting that zinc has no treatment benefit (9)(10)(11)(12)(13). Although the necessary role of zinc as a micronutrient in various physiological functions has been demonstrated, the molecular mechanism underlying the effects of zinc during viral infections has not been elucidated.…”
mentioning
confidence: 99%
“…After literature screening, 50 articles published between 1996 and 2022 were retained for the systematic review. The studies were conducted in the following continents: 33 in Asia, 22,26,27,29,[31][32][33][35][36][37][38][39][40][41]43,45,[47][48][49][50][51][52][53][54][57][58][59][60][61][62][65][66][67] eight in Africa, 23,25,34,42,44,55,63,68 five in South America, 20,21,24,28,46 two in North America, 56,64 one in Central America, 19 and one in Oceania. 30 Four trials were conducted ...…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Dari tiga belas studi, tujuh studi tidak memiliki data yang lengkap; tidak melaporkan kadar zink awal, [12][13][14][15][16][17] dan tidak melaporkan luaran yang diteliti. 18 Satu studi memberikan intervensi tambahan selain zink dan antibiotik standar untuk pneumonia, 19 serta satu studi setelah dilakukan telaah kritis dinilai kurang baik. 20 Dengan demikian terdapat empat artikel yang akan digunakan sebagai acuan dalam penyusunan systematic review ini.…”
Section: Hasil 31 Seleksi Studiunclassified